Pengaruh Beban Pajak, Tunneling Incentive, Exchange Rate, Ukuran Perusahaan, Dan Profitabilitas Tehadap Transfer Pricing - Muhammad Fikri Ramadhan; Rindy Citra Dewi; Asma Liza (JURNAL PUNDI, 2022)
This study aims to determine how much influence the tax burden, tunneling incentive, exchange rate, company size and profitability have on transfer pricing. The sample collection method uses purpose sampling, with a total sample of 35 companies in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The data in this study were analyzed using panel data regression analysis techniques using Eviews 10.The results obtained are: (a) the tax burden variable has no significant effect on transfer pricing (b) the tunneling incentive variable has no significant effect on transfer pricing (c) the exchange rate variable has no significant effect on transfer pricing (d) the firm size has a positive effect and significant effect on transfer pricing and (e) profitability has no significant effect on transfer pricing.